Pengaruh Metode Safinda terhadap Tingkat Pemahaman Siswa pada Mata Pelajaran Qur’an Hadits di MA Unggulan Al-Azhar Muncar Banyuwangi - Afif, Nur; Mukhtarom, Asrori; Maghfiroh, Ulfi Nailil; Qowim, Agus Nur (EduInovasi: Journal of Basic Educational Studies, 2024)
This research aims to determine the influence of the Safinda method on the level of student understanding of the Qur'an Hadith at MA Unggulan Al Azhar Muncar Banyuwangi. This research uses a quantitative approach with a descriptive type of quantitative research. The population used in this study was all students at MA Unggulan Al Azhar Muncar Banyuwangi which amounted to 140 students. While the number of samples in this study was 25 students. Data collection techniques in this study are by using observation before research, interviews, questionnaires, and documentation. Based on the results of the study, the calculated value of > rtable or 0.544 > 0.396 at the level of significance of 5%, Ho was rejected or there was a sinister positive influence between the Safinda method on the level of student understanding of the Qur'an Hadith subject at the Flagship MA Unggulan Al Azhar Muncar Banyuwangi. Keywords: Safinda Method, Learning Method, Level of Understanding